2014
DOI: 10.1590/0104-6632.20140314s00002677
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salts on the coexistence curve and protein partitioning in nonionic aqueous two-phase micellar systems

Abstract: -Aqueous two-phase micellar systems (ATPMS) can be exploited in separation science for the extraction/purification of desired biomolecules. Prior to phase separation the surfactant solution reaches a cloud point temperature, which is influenced by the presence of electrolytes. In this work, we provide an investigation on the cloud point behavior of the nonionic surfactant C 10 E 4 in the presence of NaCl, Li 2 SO 4 and KI. We also investigated the salts' influence on a model protein partitioning. NaCl and Li 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Their study demonstrated that knowledge of the electrolyte influence in this type of system is essential to perform partitioning studies. Furthermore, the correct choice of salt to be added can be pivotal to identify certain temperature conditions, thus allowing the achievement of more extreme or lower temperatures …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study demonstrated that knowledge of the electrolyte influence in this type of system is essential to perform partitioning studies. Furthermore, the correct choice of salt to be added can be pivotal to identify certain temperature conditions, thus allowing the achievement of more extreme or lower temperatures …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the correct choice of salt to be added can be pivotal to identify certain temperature conditions, thus allowing the achievement of more extreme or lower temperatures. 45 In a study conducted by Amid and colleges, the effectiveness of different types and concentrations of nonionic surfactants (Pluronic series and X-114) on the partitioning behavior of the serine protease from kesinai leaves was evaluated. Their results showed that the enzyme preferentially partitioned into the bottom surfactant-rich phase.…”
Section: Extraction In Aqueous Two-phase Micellar Systemmentioning
confidence: 99%
“…The %AB Lip of L. scottii L117 lipase ranged between 84.7% and 113% at 25.0 and 28.0°C in preliminary assays with the micellar system. An %AB Lip loss of 15% is considered acceptable in ATPS purification processes [31], therefore, we proceeded with our assessments using the nonionic surfactant TX-114 system for L. scottii L117 lipase extraction. The high 113.0% value may be related to a decrease in lipase inhibitor concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This affinity may be a reflection of hydrophobic interaction between micelle core and hydrophobic lipase surface [10]. In ATPMS, when the surfactant reaches a critical micelle concentration (CMC), micelles form in the aqueous solution following different geometric organizations such as lamellar, spherical, cubical, and planar [10,16,31], and polymeric system arrange themselves with different exclusion volume effect characteristics among system conditions and types. Therefore, polymeric and micellar system present different available volume to molecules partition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation